Unintended Consequences 2016
DOI: 10.22459/uc.08.2016.03
|View full text |Cite
|
Sign up to set email alerts
|

Intertwined Mobilities of Education, Tourism and Labour: The Consequences of 417 and 485 Visas in Australia

Abstract: 1This chapter focuses on some of the consequences of recent expansions to skilled temporary graduate (subclass 485) and working holiday (subclass 417) visa programs in Australia. These visa categories allow for extended periods of work and residence, primarily among young people who are seeking an overseas work/life experience or a pathway to more permanent migration. Using data from a pilot study into the life and work experiences of 485 and 417 workers in Australia, the chapter explores the complex and heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…In a larger study focussed specifically on the experiences of accounting graduates seeking permanent skilled visas, Frost, Fan et al (2019) similarly identified a tendency to prioritise test preparation and repeat test taking over efforts to gain employment and to engage in social activities, which in this case was also driven in part by obstacles to employment for temporary visa holders in the accounting profession. These findings are consistent with an earlier study by Robertson (2016), who cites an example of a graduate who had gained employment as an accountant on a temporary visa but felt compelled to leave the position in order to focus on test preparation, so as to acquire a permanent visa as a means of gaining certainty over her residency status, and also of widening career options.…”
Section: Migrant Experiences Of Immigration Policy Driven Testingsupporting
confidence: 91%
See 1 more Smart Citation
“…In a larger study focussed specifically on the experiences of accounting graduates seeking permanent skilled visas, Frost, Fan et al (2019) similarly identified a tendency to prioritise test preparation and repeat test taking over efforts to gain employment and to engage in social activities, which in this case was also driven in part by obstacles to employment for temporary visa holders in the accounting profession. These findings are consistent with an earlier study by Robertson (2016), who cites an example of a graduate who had gained employment as an accountant on a temporary visa but felt compelled to leave the position in order to focus on test preparation, so as to acquire a permanent visa as a means of gaining certainty over her residency status, and also of widening career options.…”
Section: Migrant Experiences Of Immigration Policy Driven Testingsupporting
confidence: 91%
“…As discussed above, the layered policy space, where English score requirements are engaged for different purposes by governments, professional bodies, and employers, all test users, creates an impetus for migrants to strive for IELTS 8. Research thus far into the experiences of migrants in this context has demonstrated that such aspirations come at a significant cost, in terms of both time, money, and de-skilling (e.g., Frost, 2017;Gribble, 2014;Robertson, 2016). Frost (2017), based on a longitudinal study of the experiences of four skilled migrants taking English tests for the purpose of gaining permanent residency in Australia, found that inconsistencies between English test experiences and communicative experiences at work and in social settings led to perceptions that score requirements were arbitrary.…”
Section: Migrant Experiences Of Immigration Policy Driven Testingmentioning
confidence: 99%
“…I first outline the context of contemporary migration between Asia and Australia, highlighting how new migration policies and migrant flows have created 'staggered pathways' (Robertson, 2014(Robertson, , 2015a(Robertson, , 2016 of mobility, and then briefly outline the methods underpinning the empirical research. I then move to conceptual arguments around 'bringing time in' to the study of migrant experience and an overview of the existing work on migration and temporality that I draw on and seek to expand upon in the subsequent analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As King and Raghuram (2013) have noted, student migration outpaces international migration by four (IOM, 2008). The existing ISM scholarship covers a diverse range of topics, such as the history of ISM, the nomenclature of ‘mobility’ (vs. immigration), the globalisation and monetisation of higher education (and skilled migration transfers) and the implications of pedagogy that result from this form of migration (Brooks & Waters, 2011; Coates, 2009; Findlay et al, 2012; Friesen and Collins, 2017; Kaur Sidhu, 2017; Robertson, 2011, 2013, 2016).…”
Section: Education Agents In Ism and Immigration Infrastructures Scho...mentioning
confidence: 99%